Efektivitas Aplikasi E-Personal Dalam Meningkatkan Kinerja Pegawai (Studi Kasus di Balai Besar Pelatihan Peternakan Kota Batu) - Wahyudi, Rama; Umiyati, Sri; Tamrin, Husni (Institut Riset dan Pengembangan Indonesia, 2023)
This article aims to determine the effectiveness of the E-Personal application in improving employee performance at the Batu City Animal Husbandry Training Center (BBPP). The problem is focused on the use of E-Personal applications used by employees, where problems are found from the application and employees as users of the application. To approach this problem, Sutrisno's theoretical references are used, namely Program Understanding, Timeliness, Achieving Goals, and Real Change, Hasibuan, namely Adaptability, and S.P Siagian Availability of Facilities and Infrastructure. The data were collected through observation, interviews and documentation and analyzed qualitatively with a case study approach. This study concludes that the E-Personal application implemented at BBPP Batu city is effective, because of the nine effective sub-indicators only two are less effective, the effective sub-indicators are performance achievement, change, performance transparency, performance improvement, employee welfare. , and Applications, while the two sub-indicators that are less effective are the time to fill in the E-Personal and the Internet sub-indicator.